Enhanced Stability and Intracellular Accumulation of Quercetin by Protection of the Chemically or Metabolically Susceptible Hydroxyl Groups with a Pivaloxymethyl (POM) Promoiety - Kim, Mi Kyoung; Park, Kwang-Su; Lee, Chaewoon; Park, Hye Ri; Choo, Hyunah; Chong, Youhoon (AMER CHEMICAL SOC, 2010)
In order to increase stability of quercetin, its metabolically and chemically susceptible hydroxyl groups 7-OH and 3-OH respectively were transiently blocked with a pivaloxymethyl (POM) promoiety to provide two novel quercetin conjugates [7-O-POM-Q (2), 3-O-POM-Q (3)]. In the absence of stabilizer (ascorbic acid), the synthesized conjugates showed significantly increased stability in cell culture media [t(1/2) = 4 h (2), 52 h (3)] compared with quercetin (t(1/2) < 30 min) and quercetin prodrug 1 (t(1/2) = 0.8 h). In addition, the quercetin conjugate 2 underwent efficient cellular uptake and intracellular levels of its hydrolysis product, quercetin, were maintained up to 12 h. Stability and intracellular accumulation of 2 were demonstrated by its stabilizer-independent cytostatic effect and induction of apoptotic cell death. Even though 3 was more stable than 2, it failed to penetrate cell membranes. However, the remarkable stability of 3 warrants further investigation of quercetin conjugates with various promoieties at the 3-OH position.
Keywords: INDUCED GROWTH-INHIBITION; LOW-DENSITY-LIPOPROTEIN; IN-VITRO EVALUATION; CELL-CULTURE MEDIA; COLON-CANCER CELLS; HYDROGEN-PEROXIDE; ORAL BIOAVAILABILITY; FLAVONOID QUERCETIN; LIPID-PEROXIDATION; ANTIVIRAL ACTIVITY